Economic and political reform in developing countries - Morrissey, O; Stewart, F (Macmillan Press, 1995)
Eight papers, resulting from the 1992 Development Studies Association Annual Conference held at the University of Nottingham, examine the complex, iterative, and often chaotic two-way connections which emerge between political and economic dimensions of reform. David Seddon explores reform and popular protest in Eastern Europe. Maya Koteva discusses trade policy reform in Central and Eastern Europe. Richard M. Auty focuses on economic development and the resource curse thesis. Mark Robinson addresses aid, democracy, and political conditionality in sub-Saharan Africa. Carolyn Jenkins considers adjusting to economic sanctions in South Africa. Alexandre Rands Barros presents a structuralist evaluation of the U.S. initiatives for trade liberalization within the Americas. Frederick Nixson and John Launder assess stabex, conditionality, and the macroeconomy in the Solomon Islands. Barbara Evers examines trade liberalization and employment in Indonesia. Morrissey is at the University of Nottingham. Stewart is at the University of Oxford. Index.